Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1264/jsme2.me12146
|View full text |Cite
|
Sign up to set email alerts
|

Stress Tolerance of <i>Methylobacterium</i> Biofilms in Bathrooms

Abstract: A comprehensive survey of microbial flora within pink biofilms in bathrooms was performed. Pink biofilms develop relatively rapidly in bathrooms, can be difficult to remove, and are quick to recur. Bacterium-sized cells were found to be predominant in 42 pink biofilms in Japan using a scanning electron microscope. Methylobacterium strains were detected from all samples in bathrooms by an isolation method. To explain this predominance, 14 biofilm samples were analyzed by fluorescence in situ hybridization. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Methylobacterium sp. is well adapted to survive in a filtration environment due to its resistance to cleaning agents, which makes it the principal bacterium identified in pink bathroom biofilms (Yano et al 2013).…”
Section: The Effect Of Operating Conditionsmentioning
confidence: 99%
“…Methylobacterium sp. is well adapted to survive in a filtration environment due to its resistance to cleaning agents, which makes it the principal bacterium identified in pink bathroom biofilms (Yano et al 2013).…”
Section: The Effect Of Operating Conditionsmentioning
confidence: 99%
“…According to the literature, Methylobacterium has a strong biofilm-producing ability (28)(29)(30). Simões et al (29) tested the effects of sodium hypochlorite (liquid bleach) on the activity and culturability of Methylobacterium biofilms.…”
Section: Impact Of Biofilm Formation By Methylobacteriummentioning
confidence: 99%
“…As has already been stated, Methylobacterium is resistant to treatments with chlorine Furuhata and Koike, 1993 , detergents Yano et al, 2012, desiccation Romanovskaya et al, 2002Yano et al, 2012 andUV Romanovskaya et al, 2002 and Rhodotorula showed tolerance to ROS Sasaki et al, 2000 . M. mesophilicum has spirilloxanthin and carotenoic acids Saito et al, 1995 and R. mucilaginosa has torularhodin, -catoten, and torulene Martin et al, 2010 .…”
Section: Bactericidal and Fungicidal Effects Of Hydrogen Peroxidementioning
confidence: 89%
“…Ihara et al, 2014;Scott et al, 2004;Yano et al, 2012 and the red-pigment producing yeasts, Rhodotorula spp. Ihara et al, 2014;Hamada and Fujita, 2001;Yano et al, 2012 . The efficacies of treatments against Methylobacterium spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation